2021
DOI: 10.1186/s12967-021-02733-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of ARHGAP9: clinical implication and potential function in acute myeloid leukemia

Abstract: Background Rho GTPase activating protein 9 (ARHGAP9) is expressed in various types of cancers and can inactivate Rho GTPases that mainly regulate cytoskeletal dynamics. However, the exact role of ARHGAP9 in acute myeloid leukemia (AML) has yet to be clarified. Methods We compared the transcriptional expression, prognosis, differentially expressed genes, functional enrichment, and hub genes in AML patients on the basis of the data published in the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Despite the significantly lower expression of ARHGEF6 in CN-AML, no relationship between ARHGEF6 expression and CN-AML prognosis has been found. Furthermore, several researchers found that some genes, for example, ARHGAP9 and BCL2 were correlated with the prognosis of auto/allo-HSCT and/or chemotherapy in AML patients [3,4]. Our findings showed that auto/allo-HSCT significantly improves prognosis in patients with low ARHGEF6 expression.…”
Section: Plos Onesupporting
confidence: 57%
See 2 more Smart Citations
“…Despite the significantly lower expression of ARHGEF6 in CN-AML, no relationship between ARHGEF6 expression and CN-AML prognosis has been found. Furthermore, several researchers found that some genes, for example, ARHGAP9 and BCL2 were correlated with the prognosis of auto/allo-HSCT and/or chemotherapy in AML patients [3,4]. Our findings showed that auto/allo-HSCT significantly improves prognosis in patients with low ARHGEF6 expression.…”
Section: Plos Onesupporting
confidence: 57%
“…On the other hand, ARHGAP9, which belongs to the Rho GAP family, inactivates GTPases and oppositely function to that of Rho GEFs. ARHGAP9 is an adverse prognostic factor for AML OS [3]. Thus, Rho GEFs and Rho GAPs may play other roles in cancers.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Metascape ( http://metascape.org/gp/ ) is a gene-annotation and analysis tool commonly used in genetic research. ( Zhou et al, 2019 ; Han et al, 2021 ; Ye et al, 2021 ). The Metascape database was used to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses NMRGs.…”
Section: Methodsmentioning
confidence: 99%
“…To our surprise, a study concerning on the role of ARHGAP9 in clinical AML was just published. This study concluded that ARHGAP9 was highly expressed in AML patients associated with poor overall survival and could be used as a prognostic biomarker (Han et al, 2021). However, more biological functions of ARHGAP9 in the occurrence and development of AML remain unclear, which need an in‐depth research.…”
Section: Introductionmentioning
confidence: 99%